AN ANALYSIS OF MULTIMODAL LITERACY ON STUDENTS’ READING ABILITY AT THE VIII GRADE OF SMPN 1 KAMANG MAGEK - Dita Fitria Amanda; Reflinda Reflinda; Veni Roza; Widya Syafitri (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aimed to analyze the application of multimodal literacy to enhance the reading abilities of grade VIII students at SMPN 1 Kamang Magek. Multimodal literacy, which incorporated text, images, audio, and other media elements, served as a strategy to improve students' comprehension of English texts, offering strong potential to support reading instruction, particularly in English as a second language. Utilizing diverse media such as images, sounds, and videos was believed to increase student interest, deepen text comprehension, and boost learning motivation. Using a qualitative approach with a case study method, data were collected through observations and interviews with English teachers and six selected students. The findings revealed that integrating multimodal elements enhanced students’ engagement and comprehension in reading instruction, though teachers faced challenges, especially due to limited facilities and variations in students’ abilities. This study suggested that multimodal literacy was an effective approach for improving reading skills in English language learning, provided there was additional support through better facilities and teacher training.